الفروق في عناصر اللياقة البدنية الخاصة عند ناشئي الجمباز في الأردن تبعاً للنمط الجسمي - إرميلي، زياد محمد حسين; يوسف، إياد; الكيلاني، هاشم عدنان (الأكاديمية الدولية لتكنولوجيا الرياضة, 2019)
The purposes of this study were to identify the somatotype prevailing among the gymnast beginners in Jordan; to identify their level of skill related fitness, as well as to know the differences in the somatotype and skill related physical fitness components of these gymnasts. Thirty athletes representing 100% of the size of the original society included the participants of the gymnastics in Jordan for the age group (6-8) years. The Heath and Carter method was used to determine body type components and the level of fitness was determined by a set of tests for gymnast selection to measure fitnesscomponents. The results showed that the musculoskeletal pattern was superior to the slim and muscular dystrophy in all fitness components except for the elasticity in addition to determining the somatotype prevailing in these gymnasts. It was concluded to determine the patterns of somatotype in the selection of potential gymnastics and reliance on muscular and muscular style slim as the best somatotype of gymnastics.
هدفت هذه الدراسة إلى التعرف على الأنماط الجسمية السائدة لدى ناشئي الجمباز في الأردن وإلى مستوى اللياقة البدنية الخاصة بهم بالإضافة إلى معرفة الفروق في الأنماط الجسمية ومستوى عناصر اللياقة البدنية الخاصة لديهم. اشتملت عينة الدراسة على ناشئي الجمباز في الأردن للفئة العمرية (6-8) سنوات حيث بلغ حجم العينة 30 ناشئ يمثلون ما نسبته 100% من حجم المجتمع الأصلي حيث تم اختيارهم بالطريقة العمدية. استخدمت طريقة هيث وكارتر لتحديد مكونات النمط الجسمي وتم التعرف على مستوى اللياقة البدنية من خلال مجموعة من الاختبارات الخاصة باختيار ناشئ الجمباز لقياس عناصر اللياقة البدنية. أظهرت النتائج تفوق النمط العضلي على النمط العضلي النحيف والنحيف العضلي في جميع عناصر اللياقة البدنية الخاصة باستثناء عنصر المرونة بالإضافة إلى تحديد الأنماط الجسمية السائدة لدى هؤلاء اللاعبين. وعلى ضوء ذلك يوصى بضرورة تحديد الأنماط الجسمية عند انتقاء ناشئ الجمباز والاعتماد على النمط العضلي والعضلي النحيف كأفضل الأنماط الجسمية لممارسة رياضة الجمباز.
Keywords: اللياقة البدنية -- التمرينات الرياضية -- الجمباز -- الأردن